2021
DOI: 10.12998/wjcc.v9.i33.10075
|View full text |Cite
|
Sign up to set email alerts
|

Utility of cooling patches to prevent hand-foot syndrome caused by pegylated liposomal doxorubicin in breast cancer patients

Abstract: BACKGROUND Pegylated liposomal doxorubicin (PLD) uses the hydrophilic layer of liposomes to reach the sweat on the skin surface or accumulate in the sweat glands, producing toxic free radicals and oxidative damage, resulting in hand-foot syndrome (HFS). Regional cooling can induce vasoconstriction to reduce the release of drugs in the limbs and reduce the accumulation of drugs in sweat glands; thus, decreasing the incidence and severity of HFS. AIM To study the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…56 Emollients have been used to treat this, but limited studies have shown that cooling patches and henna are effective treatments. 56,57 Patients treated with paclitaxel, a taxane, should be monitored for peripheral neuropathy. 58 Some patients undergoing chemotherapy may feel unwell and present in primary care, ambulatory biopsy of a lymph node is preferred.…”
Section: Diagnostic Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…56 Emollients have been used to treat this, but limited studies have shown that cooling patches and henna are effective treatments. 56,57 Patients treated with paclitaxel, a taxane, should be monitored for peripheral neuropathy. 58 Some patients undergoing chemotherapy may feel unwell and present in primary care, ambulatory biopsy of a lymph node is preferred.…”
Section: Diagnostic Interventionsmentioning
confidence: 99%
“…Hand-foot syndrome, or palmar–plantar erythrodysesthesia, is another adverse effect that patients receiving liposomal doxorubicin may report. Hand-foot syndrome causes erythema, swelling, blisters, and paresthesia in the hands and feet 56. Emollients have been used to treat this, but limited studies have shown that cooling patches and henna are effective treatments 56, 57.…”
Section: Management and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, ROS attack keratinocytes and trigger release of in ammatory cytokines that lead to the onset of HFS [21]. Regional cooling has been the most common strategy for the primary prevention of HFS [22][23][24][25]. Cooling of the wrists and ankles during PLD administration constricts blood vessels, thus reducing blood ow to the hands and feet.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the distribution of PLD to the hands or feet is decreased and HFS can be prevented. However, the e cacy of cooling for prevention of HFS associated with PLD is controversial; up to 30% and 17% of patients received cooling reportedly developed HFS ≥ Grade 2 and ≥ Grade3, respectively [22][23][24][25], indicating that cooling alone is insu cient in preventing HFS associated with PLD. Meanwhile, oral steroid therapy has been recommended as a secondary preventive therapy [26].…”
Section: Introductionmentioning
confidence: 99%